2013
DOI: 10.1007/s11003-013-9596-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cetyltrimethylammonium Chloride on the Strength of Silica Optical Fibers

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The higher the viscosity, the lower is the solvation of BAC and CTAC and then the lower is the micellization and cmc. In water at 298 K, it was found that the cmc of BAC and CTAC agrees with the literature value. , …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The higher the viscosity, the lower is the solvation of BAC and CTAC and then the lower is the micellization and cmc. In water at 298 K, it was found that the cmc of BAC and CTAC agrees with the literature value. , …”
Section: Resultssupporting
confidence: 87%
“… a The values in bold are from ref , while values in parenthesis are from surface tension measurements. Standard uncertainties, u , of cmc is u (cmc) = 0.0002 mol L –1 . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a. CTAC presents the first CMC at 1.3 mM in ambient conditions, 9 and it is experimentally found to exhibit a rich phase behaviour in a wide range of concentrations and temperatures. Reiss-Husson and Luzzati 10 studied the self-assembly of, among others, CTAC pure aqueous solutions using X-ray diffraction (XRD) technique.…”
Section: Introductionmentioning
confidence: 99%
“…El Abdi et al [11,12] have studied the effect of different surfactants on the strength of silica optical fibers. But fibers were aged during small aging durations and in ambient temperature.…”
Section: Introductionmentioning
confidence: 99%